PERAN PEMERINTAH DESA DALAM PEMBANGUNAN INFRASTRUKTUR DI DESA TEGALSARI KECAMATAN PLERED KABUPATEN CIREBON - Indri Wulandari; Eka Wildanu; Sastra Abijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2025)
Village infrastructure development is crucial to improving community welfare and enhancing inter-regional accessibility. The village government plays a strategic role in managing this development, particularly in providing village roads that support the community's social and economic activities. This study aims to analyze the role of the village government in infrastructure development in Tegalsari Village, Plered District, Cirebon Regency. A descriptive qualitative research method was employed, utilizing data collection techniques such as observation, interviews, and documentation. Research informants included the Village Head, village officials, the Village Consultative Body (BPD), the Village Community Empowerment Institute (LPMD), neighborhood/hamlet association heads (RT/RW), community leaders, and religious leaders. The findings indicate that the village government acts as a motivator, facilitator, and mobilizer. As a motivator, the village government encourages active community participation; as a facilitator, it provides development facilities and infrastructure; and as a mobilizer, it harnesses the community's full potential to engage in development efforts. The development process is carried out in a participatory and efficient manner, concluding with structured oversight. Challenges encountered include limited budgets and supporting resources. In conclusion, while the village government's role in Tegalsari Village is functioning well, there is a need to optimize synergy among the village government, the community, and village institutions to ensure more sustainable development.